Using Forbush Decreases to Derive the Transit Time of ICMEs Propagating from 1 AU to Mars. Issue 1 (18th January 2018) - Freiherr von Forstner, Johan L.; Guo, Jingnan; Wimmer‐Schweingruber, Robert F.; Hassler, Donald M.; Temmer, Manuela; Dumbović, Mateja; Jian, Lan K.; Appel, Jan K.; Čalogović, Jaša; Ehresmann, Bent; Heber, Bernd; Lohf, Henning; et al.
Abstract: The propagation of 15 interplanetary coronal mass ejections (ICMEs) from Earth's orbit (1 AU) to Mars (∼1.5 AU) has been studied with their propagation speed estimated from both measurements and simulations. The enhancement of magnetic fields related to ICMEs and their shock fronts causes the so‐called Forbush decrease, which can be detected as a reduction of galactic cosmic rays measured on ground. We have used galactic cosmic ray (GCR) data from in situ measurements at Earth, from both STEREO A and STEREO B as well as GCR measurements by the Radiation Assessment Detector (RAD) instrument on board Mars Science Laboratory on the surface of Mars. A set of ICME events has been selected during the periods when Earth (or STEREO A or STEREO B) and Mars locations were nearly aligned on the same side of the Sun in the ecliptic plane (so‐called opposition phase). Such lineups allow us to estimate the ICMEs' transit times between 1 and 1.5 AU by estimating the delay time of the corresponding Forbush decreases measured at each location. We investigate the evolution of their propagation speeds before and after passing Earth's orbit and find that the deceleration of ICMEs due to their interaction with the ambient solar wind may continue beyond 1 AU. We also find a substantial variance of the speed evolution among different events revealing the dynamic and diverse nature of eruptive solar events. Furthermore, the results are compared to simulation data obtained from two CME propagation models, namely the Drag‐Based Model and ENLIL plus cone model. Plain Language Summary: Eruptions from the Sun often containing a shock front followed by a magnetic ejecta may cause a depression in the omnipresent cosmic rays that can now be observed at Mars thanks to the radiation assessment detector (RAD) on board the Mars Science Laboratory. When both Earth (or other spacecraft like STEREOs that are located at Earth orbit) and Mars are closely aligned on the same side of the Sun, we have a great opportunity to observe such eruptions passing by and affecting both planets. Based on measurements from both Earth orbit and Mars, we have studied 15 solar events and their properties such as the speed and its evolution from the Sun to Mars. We found that most of these eruptions slow down considerably during their propagation from the Sun to Earth orbit and even beyond all the way to Mars. Key Points: The interplanetary propagation of 15 CMEs is studied based on a cross‐correlation analysis of Forbush decreases at 1 AU and Mars The speed evolutions of the ICMEs are derived from observations, indicating that most of them are slightly decelerated even beyond 1 AU Model‐predicted ICME arrival times at Mars could be improved by using ICME parameters measured at 1 AU